Non-Invasive Prenatal Testing (NIPT) in pregnancies with trisomy 21, 18 and 13 performed in a public setting – factors of importance for correct interpretation of results. (July 2018) - Hartwig., Tanja S; Ambye, Louise; Werge, Lene; Weiergang, Martin Kenneth; Nørgaard, Pernille; Sørensen, Steen; Jørgensen, Finn Stener
Abstract: Objectives: We have established an open source platform for non-invasive prenatal testing (NIPT) based on massively parallel whole-genome sequencing in a public setting. The objective of this study was to investigate factors of importance for correct interpretation of NIPT results to ensure a high sensitivity and specificity. Study design: This investigation is a retrospective case-control study performed in a public NIPT center. The study included 108 aneuploid cases and 165 euploid controls. MPS was performed on circulating cell-free DNA in maternal blood. The pipeline included automated library preparation and sequencing on a HiSeq1500 (Illumina). The software programmes WISECONDOR and SeqFF were used for data analysis of aneuploidy status and fetal fraction of cell-free DNA, respectively. Lower limit of fetal fraction for aneuploidy testing was 0.02. Results: We identified four false negative aneuploidy cases of which two were explained by a vanishing twin. The number of no-call cases due to low fetal fraction was 8 out of 273 (2.9%). The sensitivity and specificity, when no-calls and vanished twins were excluded, were 100% and 99.5% for T21, 91% and 99.2% for T18, and 100% and 99.6% for T13. By multiple regression analysis we found a significant association between fetal fraction and gestational age, maternal BMI and ART treatment. Conclusion: With a non-commercial open source NIPT set-up having the same high test-performance as reported by large private laboratories, we show that fetal fraction, a vanishing twin, BMI, gestational age and ART treatment are important factors in the interpretation of NIPT results.